Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the quadratic equation [tex]\((x-3)(x+2) = 0\)[/tex], we can use the Zero Product Property, which states that if the product of two factors is zero, then at least one of the factors must be zero.
Given the equation:
[tex]\[ (x - 3)(x + 2) = 0 \][/tex]
We can set each factor equal to zero and solve for [tex]\(x\)[/tex]:
1. For the first factor:
[tex]\[ x - 3 = 0 \][/tex]
Add 3 to both sides to isolate [tex]\(x\)[/tex]:
[tex]\[ x = 3 \][/tex]
2. For the second factor:
[tex]\[ x + 2 = 0 \][/tex]
Subtract 2 from both sides to isolate [tex]\(x\)[/tex]:
[tex]\[ x = -2 \][/tex]
So, the solutions to the equation [tex]\((x-3)(x+2) = 0\)[/tex] are [tex]\(x = 3\)[/tex] and [tex]\(x = -2\)[/tex].
The solution with the lowest value is:
[tex]\[ x = -2 \][/tex]
Given the equation:
[tex]\[ (x - 3)(x + 2) = 0 \][/tex]
We can set each factor equal to zero and solve for [tex]\(x\)[/tex]:
1. For the first factor:
[tex]\[ x - 3 = 0 \][/tex]
Add 3 to both sides to isolate [tex]\(x\)[/tex]:
[tex]\[ x = 3 \][/tex]
2. For the second factor:
[tex]\[ x + 2 = 0 \][/tex]
Subtract 2 from both sides to isolate [tex]\(x\)[/tex]:
[tex]\[ x = -2 \][/tex]
So, the solutions to the equation [tex]\((x-3)(x+2) = 0\)[/tex] are [tex]\(x = 3\)[/tex] and [tex]\(x = -2\)[/tex].
The solution with the lowest value is:
[tex]\[ x = -2 \][/tex]
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.